Reconfigurable Cryptographic Processor - Liu, Leibo; Wang, Bo.; Wei, Shaojun; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book focuses on the design methods for reconfigurable computing processors for cryptographic algorithms. It covers the dynamic reconfiguration analysis of cryptographic algorithms, hardware architecture design, and compilation techniques for reconfigurable cryptographic processors, and also presents a case study of implementing the reconfigurable cryptographic processor "Anole" designed by the authors' team. Moreover, it features discussions on countermeasures against physical attacks utilizing partially and dynamically reconfigurable array architecture to enhance security, as well as the latest trends for reconfigurable cryptographic processors. This book is intended for research scientists, graduate students, and engineers in electronic science and technology, cryptography, network and information security, as well as computer science and technology.
Introduction -- Analysis of Reconfigurability of Cryptographic Algorithms -- Hardware Architecture -- Compilation Techniques -- Case Studies in Design -- Countermeasures against Physical Attacks -- Perspective: Application Trends.
Keywords: Signal processing; Cryptography; Data encryption (Computer science).; Microprocessors; Computer architecture; Telecommunication; Algorithms; Coding theory; Information theory; Signal, Speech and Image Processing; Cryptology; Processor Architectures; Communications Engineering, Networks; Algorithms; Coding and Information Theory